Causes of tax evasion and their relative contribution in Malaysia: an artificial neural network method analysis - Razieh Tabandeh; Mansor Jusoh; Nor Ghani Md. Nor; Mohd Azlan Shah Zaidi (Penerbit Universiti Kebangsaan Malaysia, 2013)
Tax is one means of financing government expenditures and plays an important role in increasing government revenue. The amount of tax collected actually depends on the effectiveness of the tax system in an economy. When a taxation system is ineffective, many people will exploit the situation to avoid paying tax and tax evasion will become popular. In the presence of tax evasion, the government cannot allocate revenue for programs or provide desirable social services. Realizing the significant impact of tax evasion on the economy, the present study aims to determine the main factors that result in tax evasion and their relative importance. The present study employs an artificial neural network (ANN) methodology on Malaysian data for the period between 1963 and 2011. The results show that tax burden, size of the government and inflation rate have positive effects on tax evasion. The income of taxpayers and trade openness, however, has negative effects on tax evasion. The results also reveal that the income of the taxpayer has a more significant relationship with levels of tax evasion than the other causes of tax evasion examined in the present study.